(untitled) (Delta Medical College Journal, 2024)
Background: Tamarindus indica is an antioxidant rich plant. It has therapeutic interest in drugs and xenobiotics induced liver damage. Objective: This study was aimed to explore the effectiveness of ethanolic extract of seed of Tamarindus indica on liver weight when liver is intoxicated with paracetamol and to compare it with the effects of Vitamin E, a known hepatoprotectant. Materials and method: A total of twenty four Long Evan’s rats were collected and divided into four groups. Each group having six rats (n=6). Control group received normal diet ad libitum, only paracetamol group received paracetamol (1500 mg/kg) for 12 days and rest two groups received paracetamol (1500 mg/kg) along with ethanolic extract of seed of Tamarindus indica (1250 mg/kg) and vitamin E (500 mg/kg) for 12 days respectively. On 13th day, all rats were sacrificed. Then livers were collected and weighed by an electronic balance. Results: In this study, the mean (±SD) liver weight was 4.08±0.23 in control group, 6.27±0.68 in only paracetamol treated group, 5.22±0.72 and 4.57±0.86 in paracetamol along with seed extract of Tamarindus indica and vitamin E treated group respectively. Conclusion: The present study showed that mean (±SD) weight of liver increased with paracetamol and decreased with seed extract of Tamarindus indica which is similar to the effects of vitamin E. Delta Med Col J. Jan 2021;9(2): 80-83